Phase-field simulations of grain boundary grooving under diffusive-convective conditions. (1st February 2021) - Laxmipathy, V. Pavan; Wang, Fei; Selzer, Michael; Nestler, Britta
Graphical abstract: Abstract: Grain boundaries are potential sites for the development of morphological instabilities along a solidifying interface, and play an important role in the microstructural properties of cast alloys. In the present study, we employ a multiphase-field model to address the grain boundary grooving phenomenon under the cooperative effect of convection and volume diffusion in the liquid phase. Under pure diffusive conditions, we first benchmark our phase-field model by illustrating and comparing the formation of symmetric groove profiles across the grain boundary with Mullins's groove. In the presence of an additional convective transport mechanism, we systematically depict that the asymmetricity of groove profile increases with the increase in the convection velocity. Particularly, it is identified that the groove kinetics as well as the grain boundary grooving mechanism is significantly modified in the diffusive-convective regime. The present two-dimensional simulations, while providing considerable insights into the mechanism of grain boundary grooving, also closes the gap with the experimental and theoretical observations reported earlier. In addition, the role of relative surface energies on the groove deepening along with the ridge morphology is discussed in detail. The simulated grain boundary features are of practical significance for understanding and controlling the nanocrystalline thin film experiments.